HUBUNGAN METODE KOMUNIKASI EFEKTIF SITUATION BACKGROUND ASSESSMENT RECOMMENDATION (SBAR) DENGAN PENERAPAN BUDAYA KESELAMATAN PASIEN DI RUANG RAWAT INAP RUMAH SAKIT AMINAH TANGERANG - Fahrida Cahayu; Seriga Banjarnahor (STIKes Murni Teguh, 2023)
The SBAR effective communication method is an effective communication framework to improve patient safety. The second is effective communication. The implementation of effective communication methods at Aminah Hospital has not been perfect for nurses. This research was conducted to find out whether there is a relationship between the effective communication method of SBAR and the implementation of patient safety culture. This type of quantitative research with analytic study and cross-sectional design. A sample of 40 people used purposive sampling technique. The instrument used for the SBAR communication method was from the Indonesian Ministry of Health PPSDMK assessment format and the patient safety culture standard questionnaire from AHRQ. The SBAR observation data was carried out when the nurse was doing a handover between shifts, followed by filling in the questionnaire. Then the data obtained was processed and the data were analyzed univariately and bivariately with the chi-square test. The value of p = 0.044 is obtained. The result of p value < 0.05 (Sig 95%) then Ho is rejected, and Ha is accepted, so there is a relationship between the effective SBAR communication method and the application of patient safety culture. It is recommended that Aminah Hospital continue to improve the application of the SBAR communication method when carrying out handovers. Abstrak Metode komunikasi efektif SBAR merupakan kerangka komunikasi efektif untuk meningkatkan keselamtan pasien yang kedua yaitu komunikasi efektif. Pelaksanaan metode komunikasi efektif di Rumah Sakit Aminah belum sempurna dilakukan perawat. Dilakukan penelitian ini untuk mengetahui apakah ada hubungan metode komunikasi efektif SBAR dengan penerapan budaya keselamatan pasien. Jenis penelitian kuantitatif dengan studi analitik dan desain cross sectional. Sampel sebanyak 40 orang menggunakan tehnik purpose sampling. Instrumen yang digunakan untuk metode komunikasi SBAR dari format penilaian badan PPSDMK Kemenkes RI dan kuesioner baku budaya keselamatan pasien dari AHRQ. Data observasi SBAR dilakukan saat perawat melakukan handover antar shif, dilanjutkan dengan pengisian kuisioner. Kemudian data yang didapat diolah dan data dianalisis secara univariat dan bivariat dengan uji chi-square. Didapatkan nilai p = 0,044. Hasil p value < 0,05 (Sig 95%) maka Ho ditolak dan Ha diterima, sehinga ada hubungan antara metode komunikasi efektif SBAR dengan penerapan budaya keselamatan pasien. Disarankan kepada Rumah Sakit Aminah terus meningkatkan penerapan metode koumikasi SBAR saat melakukan handover.